DEMAND ILLUSION AS A WAY TO REDUCE COSTS - Kirill N. Sosnovskij (Statistika i Èkonomika, 2016)
Article devoted to a technique that reduces costs to retailers, as well as increase the speed of discounted products. This article deals with the laws of visual merchandising that have a significant impact on the implementation of the company’s products. The analysis of the first law, with the subsequent introduction into it of a new additional method. Consider the effect of «Illusion of deficit» arising from the application of the proposed method. The article also defines the basic hypothesis of the existence of methods and effect, and the conditions for their effective implementation. To confirm the effectiveness of the developed method, quantitative surveys are conducted for different age groups creating situational model, which allows respondents to feel as a consumer.